2015
DOI: 10.1002/esp.3700
|View full text |Cite
|
Sign up to set email alerts
|

Dune deformation in a multi‐directional wind regime: White Sands Dune Field, New Mexico

Abstract: As with most dune fields, the White Sands Dune Field in New Mexico forms in a wind regime that is not unimodal. In this study, crescentic dune shape change (deformation) with migration at White Sands was explored in a time series of five LiDAR‐derived digital elevation models (DEMs) and compared to a record of wind direction and speed during the same period. For the study period of June 2007 to June 2010, 244 sand‐transporting wind events occurred and define a dominant wind mode from the SW and lesser modes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…While not exact, a unidirectional approximation for both the dune migration direction and wind direction is reasonable. Wind speeds above threshold are strongly unimodal (from the Southwest) and the majority of dune migration occurs along these SW winds (Jerolmack et al, ; Pedersen et al, ). Previous research has identified three regions associated with differing sediment transport and dune dynamics (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…While not exact, a unidirectional approximation for both the dune migration direction and wind direction is reasonable. Wind speeds above threshold are strongly unimodal (from the Southwest) and the majority of dune migration occurs along these SW winds (Jerolmack et al, ; Pedersen et al, ). Previous research has identified three regions associated with differing sediment transport and dune dynamics (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Soft‐sediment deformation is a disruption of unlithified sediments (Alsop et al, ; Owen et al, ; Van Loon, ) and is widely documented in both subaerial (McKEE et al, ; Moretti, ; Pedersen et al, ) and subaqueous environments (Avşar et al, ; Gladkov et al, ; Jiang et al, ; Sims, ). Commonly, the disturbances are triggered either by seismic shaking (Liu‐Zeng et al, ; Monecke et al, ; Sakaguchi et al, ; Sims, ; Strasser, Kölling, et al, ) or by nonseismic triggers, for example, tides (Greb & Archer, ), storm waves (Molina et al, ), floods (Li et al, ), and sediment overloads (Moretti et al, ; Moretti & Sabato, ).…”
Section: Introductionmentioning
confidence: 99%
“…() and Pedersen et al . (). All time‐series components were georeferenced and co‐registered in ESRI ArcMap ™ .…”
Section: Methodsmentioning
confidence: 99%
“…The crescentic dunes average 4·7 m in height (Baitis et al ., ), crestline length averages 247 m, dune spacing averages 136 m and crestline orientation is 345° (Ewing et al ., ), which is borderline transverse (classification of Hunter et al ., ) to the net resultant of the wind towards 065° (Reitz et al ., ; Jerolmack et al ., ). Crescentic dune behaviour consists of crest‐normal migration at ca 3·5 m yr −1 under strongly dominant south‐westerly winds, but there is also along‐crest migration of dune sinuosity to the south‐east because of a secondary mode of NNW winds (Pedersen et al ., ). A tertiary wind mode from the SSE gives rise to ephemeral crestal slipface reversals (Pedersen et al ., ).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation